Alguns aspectos do conceito winnicottiano de neurose - Cardoso, Cristiano Cemin (2005)
ABSTRACT This study aims at clarifying some aspects related to the concept of neurosis according to Donald Winnicott (1896-1971), an English pediatrician and psychoanalyst, who considered the study of this concept submitted to the investigation of the human maturational processes which are not defined by a theory of sexual development, as it was proposed by Freud. Firstly, I concentrate this study on Freud s concept of neurosis, clarifying his clinical and meta-psychoanalytical data throughout his work, to show afterwards, a new form of conceiving the neuroses inside the human maturational process. Explaining the human development without the support of the drive theory, Winnicott points to the good-enough care as something that guarantees a complete development of infantile levels, which is the basis for thinking about the possibility of a neurosis manifestation. There is a corporal way of the instinctive excitements, that will be only integrated at the moment this instinctuality makes any personal sense in the concerning stage. In this sense, the pre genital, phallic and genital organizations will be reconsidered according to the new frame. In this study, I expose that the etiology of neuroses, according to Winnicott, is located in a determined moment of the maturational process, i.e. the moment in which the triangular relationships are already possible with whole people. I make use of fragments from clinical cases attended by Winnicott to illustrate such considerations. Nevertheless, the neurotic disturbance can happen associated with other disturbances, or even to an anti social tendency that brings the notion of a clinical frame in which the neurosis doesn t appear in its pure form. Using Winnicott s frame of castration defenses, I point out to the differences between the regression of neurosis and the regressions related to the concern stage. Finally, I retake the differences between the concept of neurosis in Freud and Winnicott that happen as a consequence of a paradigmatic change in the patterns proposed by Thomas S. Kuhn.